(3x-40)+(2x-10)=90

Simple and best practice solution for (3x-40)+(2x-10)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-40)+(2x-10)=90 equation:


Simplifying
(3x + -40) + (2x + -10) = 90

Reorder the terms:
(-40 + 3x) + (2x + -10) = 90

Remove parenthesis around (-40 + 3x)
-40 + 3x + (2x + -10) = 90

Reorder the terms:
-40 + 3x + (-10 + 2x) = 90

Remove parenthesis around (-10 + 2x)
-40 + 3x + -10 + 2x = 90

Reorder the terms:
-40 + -10 + 3x + 2x = 90

Combine like terms: -40 + -10 = -50
-50 + 3x + 2x = 90

Combine like terms: 3x + 2x = 5x
-50 + 5x = 90

Solving
-50 + 5x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '50' to each side of the equation.
-50 + 50 + 5x = 90 + 50

Combine like terms: -50 + 50 = 0
0 + 5x = 90 + 50
5x = 90 + 50

Combine like terms: 90 + 50 = 140
5x = 140

Divide each side by '5'.
x = 28

Simplifying
x = 28

See similar equations:

| x(2x-3)=23 | | (7x6/3)x3-(2+3-4) | | -4(-6y-17)-11y=9(18y-9) | | (5x-1)7=-2 | | 5x=56+6 | | 20x=16x+15 | | y=-6/5(-4)+31/5 | | 6x+x/3+18 | | z/8=-26 | | (X-4)(2x+5)=o | | -1/8(n+6)=-1/9(n+2) | | (4z-10)+1z=90 | | (6x+10)/11=-4 | | 7/(4x-1)=2/(x+5) | | -6/5(-4)+31/5 | | 15=6a-24-9a | | 7-3x=1/4(8x-12) | | 2T=T-(84*.5) | | 6x^7/5-66=0 | | 9xy^2*9x^5y^2= | | 6m+9(2-m)=2(7-4m)-11 | | 15(x^2+2x)= | | 1+999= | | 3+6(7n+3)=-147 | | 4(9-3)/(8-2) | | 18(-y-2)-4(-9+3y)+76=-14 | | 9x+4+3x=7x+x+14 | | -3/4(-x-8)=x+10 | | y=8+2z | | -4/5(z+3)=-2/3(z-4/5) | | a=(w)(3w) | | 3y+2-4y=9 |

Equations solver categories